Treatment Outcomes in Completely Resected Stage I to Stage IV Uterine Carcinosarcoma With Rhabdomyosarcoma Differentiation. Issue 9 (1st November 2013) - Makker, Vicky; Kravetz, Sara J.; Gallagher, Jacqueline; Orodel, Oana-Paula; Zhou, Qin; Iasonos, Alexia; DeLair, Deborah; Aghajanian, Carol; Hensley, Martee L.
Abstract : Objective: To evaluate overall survival (OS) and progression-free survival (PFS) after adjuvant therapy in stage I to stage IV uterine carcinosarcoma with rhabdomyosarcoma differentiation. Methods: Memorial Sloan-Kettering Cancer Center medical records from 1990 to 2012 were reviewed. Patients who received chemotherapy with or without radiation therapy (RT), or RT alone, for completely resected stage I to stage IV uterine carcinosarcoma with rhabdomyosarcoma differentiation were included. Results: Of 53 patients, International Federation of Gynecology and Obstetrics stage distribution was as follows: I, 13 (24.5%); II, 8 (15.1%); III, 13 (24.5%); and IV, 19 (35.9%). Forty-one (77.4%) of 53 patients received adjuvant chemotherapy, and 34% of the patients who received chemotherapy also received pelvic RT or intravaginal brachytherapy (IVRT). Twelve (22.6%) of the 53 patients received only pelvic RT with/without IVRT. Paclitaxel-carboplatin was the most commonly used adjuvant chemotherapy treatment. The median PFS for the entire cohort was 13.4 months (95% confidence interval [CI], 10.5–17.0). The median OS for the entire cohort was 23.0 months (95% CI, 16.9–34.3). The median PFS periods by stage were 15.9 months for stages I/II versus 11.2 months for stages III/IV ( P = 0.012). Median OS was not reached in the early-stage cohort. The median OS for the late-stage cohort was 20.9 months ( P = 0.004). The median PFS periods by treatment were 10.4 months for pelvic RT with/without IVRT group versus 13.1 months for chemotherapy with/without pelvic RT with/without IVRT group ( P = 0.498). The median OS periods by treatment were 23.6 months for chemotherapy with/without pelvic RT with/without IVRT group versus 16.9 months for pelvic RT with/without IVRT group ( P = 0.501). Conclusion: The results suggest that chemotherapy alone or in combination with RT is associated with longer PFS and OS compared to RT alone. Only the stage of disease significantly affected PFS and OS.